We cover every section of the GMAT with in-depth lessons, 5000+ practice questions and realistic practice tests.

## Up to 90+ points GMAT score improvement guarantee

### The best guarantee you’ll find

Our Premium and Ultimate plans guarantee up to 90+ points score increase or your money back.

## Master each section of the test

### Comprehensive GMAT prep

We cover every section of the GMAT with in-depth lessons, 5000+ practice questions and realistic practice tests.

## Schedule-free studying

### Learn on the go

Study whenever and wherever you want with our iOS and Android mobile apps.

# Plugging In: Basic Technique

If $$a$$ is a positive even integer and $$b$$ is a positive odd integer where $$b \gt a$$, then the number of even integers between $$a$$ and $$b$$, inclusive, must be
Correct. [[snippet]] If you plug in $$a=2$$ and $$b=7$$ into this answer choice, you get > $$\displaystyle \frac{b-a+1}{2} = \frac{7-2+1}{2} = \frac{6}{2} = 3$$ All other answer choices are eliminated for this Plug-In because they do not match your **goal value**, so this is the right answer choice.
Incorrect. [[snippet]] If you plug in $$a=2$$ and $$b=7$$ into this answer choice, you get > $$\displaystyle \frac{b-a-1}{2} = \frac{7-2-1}{2} = \frac{4}{2} = 2$$ Eliminate this answer since it doesn't match your **goal value**.
Incorrect. [[snippet]] If you plug in $$a=2$$ and $$b=7$$ into this answer choice, you get > $$\displaystyle \frac{b-a}{2} = \frac{7-2}{2} = \frac{5}{2}$$ Eliminate this answer since it doesn't match your **goal value**.
Incorrect. [[snippet]] If you plug in $$a=2$$ and $$b=7$$ into this answer choice, you get > $$\displaystyle {b-a} = {7-2} = 5$$ Eliminate this answer since it doesn't match your **goal value**.
Incorrect. [[snippet]] If you plug in $$a=2$$ and $$b=7$$ into this answer choice, you get > $$\displaystyle \frac{b-a+1}{2}+1 = \frac{7-2+1}{2}+1 = \frac{6}{2}+1 = 4$$ Eliminate this answer since it doesn't match your **goal value**.
$$\displaystyle \frac{b-a}{2}$$
$$\displaystyle \frac{b-a-1}{2}$$
$$\displaystyle \frac{b-a+1}{2}$$
$$\displaystyle \frac{b-a+1}{2}+1$$
$$b-a$$